Contribution of the Ronggeng Warak Dance in Improving the Creative Economy Industry at Sanggar Sekar Kemuning, Pedurungan District, Semarang City - Anita Widyati; Malarsih Malarsih; Hartono Hartono (Universitas Negeri Semarang, 2024)
The Ronggeng Warak dance is a dance created at the Sekar Kemuning Studio which is located in Pedurungan District, Semarang City. The owner of Sanggar Sekar Kemuning is Mr Kasmiran. The Ronggeng Warak dance is a dance created by Mr. Kasmiran and Mr. Wijanarko. The choreographer of the Ronggeng Warak Dance was inspired by the Dugderan Ceremony which is held every year in Semarang City, usually at the Dugderan Ceremony there is a mascot, namely Warak.The Ronggeng Warak dance makes a major contribution to the development of the creative industry in Sanggar Sekar Kemuning, Pedurungan District, Semarang City. The creative economy plays a role in driving the economy, including creating income, creating new jobs and creating employment opportunities.